On the position of spatial and temporal adverbials in the Italian sentence - Eva Klímová (Echo des Etudes Romanes, 2012)
The article deals with the position of spatial and temporal adverbials in the Italian sentence from the functional sentence perspective (FSP) point of view, in comparison with English and Czech. Firstly, all the FSP factors are introduced, i.e. linearity, context, semantics, and, in the spoken language, intonation. The main attention is paid to semantics: spatial and temporal adverbials with the aim to prove that the position of these two sentence elements is closely related to their function on the Presentation scale and on the Quality scale. For this purpose more than 1500 clauses of an Italian text and its English translation have been analysed and statistically elaborated, with the aim to prove previous observations: a fairly strong tendency in Italian to organize the sentence elements in accordance with the basic distribution of communicative dynamism.